The role of the nervous system in the occurrence, development, and immune response of renal cell carcinoma - Sun, Honghong; Liu, Lu; Mao, Yuchen; Tan, Zhongyu; Li, Xuwen; Li, Guangyao (Frontiers in Immunology, 2025)
Renal cell carcinoma (RCC) represents one of the fastest-growing urological malignancies globally, with approximately 30% of patients presenting with metastatic disease at diagnosis. Despite advances in targeted therapy and immune checkpoint inhibitors, treatment resistance remains a critical challenge, largely attributed to the heterogeneous tumor microenvironment (TME). This review systematically examines the emerging role of the neuroimmune system in RCC pathogenesis and progression. The kidney receives dual innervation from sympathetic and parasympathetic systems, which undergo pathological remodeling during tumorigenesis. Novel findings from RCC preclinical models reveal that MANF protein drives sunitinib resistance via IRE1α-XBP1 pathway inhibition, while NPTX2 aberrantly activates PI3K-Akt survival signaling in clear cell renal cell carcinoma (ccRCC). Therapeutic strategies targeting the neuroimmune axis show promise, including β-blockers combined with PD-1 inhibitors to reverse T cell exhaustion, CXCR4 antagonists disrupting nerve- tumor-associated macrophage (TAM) crosstalk, and radiofrequency ablation of perirenal nerve plexus. Future directions involve spatial transcriptomics mapping of the neuroimmune landscape, developing neurotransmitter-targeted delivery systems, and optimizing sequential combination therapies. Understanding the tripartite interaction between nerves, immune cells, and tumor cells opens new avenues for precision medicine in RCC, potentially establishing neuroimmune modulation as a potential new direction of RCC therapy distinct from anti-angiogenesis and immunotherapy.